Quantum Cryptography, its Protocols and Techniques (International Journal of Engineering and Computer Science, 2015)
Various approaches and techniques are being constantly studied to ensure a secure communication. Modern cryptographic techniques face a serious threat by the progress of computing power. They generally make use of large numbers which can be factorized. The use of this make the communication vulnerable to attacks as it is now possible to reverse the one-way functions. Motivated by this concern, Quantum Cryptography was introduced to provide secure communication. It depends on two important aspects of quantum mechanics, the Heisenberg Uncertainty principle and the principle of photon polarization. This paper focuses on the principle and working of Quantum Cryptography and compares various Quantum Key Distribution Protocols such as BB84 and B92. It also introduces other cryptographic techniques which are popularly used.